Changing Northeast India Summer Monsoon Onset Dynamics in a Warming World - Simanta Das; Rahul Mahanta; Bijit Kumar Banerjee; B. N. Goswami (International Journal of Climatology, 2026)
The Indian Summer Monsoon typically begins over Northeast India (NEI) about 2 weeks earlier than monsoon onset over Kerala, extending the rainy season in NEI to around 150 days. This early onset is strongly linked to planetary‐scale processes, particularly interactions with extratropical Rossby waves. These waves facilitate the downward and southward intrusion of potential vorticity, which triggers low‐level cyclonic vorticity and initiates monsoon onset. The quasi‐biweekly oscillation further facilitates this process. While climate change is associated with a weakening of the seasonal mean monsoon over NEI, its impact on extratropical influences and the trend of earlier onset remains uncertain. This study examines changes in tropical circulation and extratropical influences by comparing two periods: 1940–1960 and 2002–2023. Results reveal a marked increase in extratropical influence in recent decades. In 2002–2023, clear signs of downward PV intrusion and enhanced low‐level cyclonic vorticity are observed, in contrast to the earlier period where such features are largely absent. Lead–lag composites of PV anomalies at 200 hPa show prominent eastward‐propagating signals during onset in the recent period. In 1940–1960, monsoon onset was primarily driven by local mesoscale convection and self‐organisation, with cyclonic vorticity strengthening 2 days post‐onset. During the earlier period, heat sources were more likely driven by local convective instability, as indicated by higher convective available potential energy, which was approximately 500 J/kg greater at the time of monsoon onset. Additionally, air‐sea interactions have become more influential in recent decades. While stronger Sea surface temperatures (SSTs) over the Bay of Bengal (BOB) during pre‐onset facilitates the onset through enhanced moisture flux, SSTs over BOB tend to cool once the onset process begins. These findings highlight a significant shift in monsoon onset mechanisms over NEI, with increasing extratropical control and evolving ocean–atmosphere interactions likely shaped by climate change.

Mangrove derived coactive bacterial inoculant triggered biochemical traits rejuvenating plant cell function under salt stress - Anwesha Chatterjee; Proma Ghosh; Simanta Das; Murali Sharaff; Somnath Mandal; Prateek Madhab Bhattacharya; Tinni Chaudhuri; Harshata Pal (Plant Cell Reports, 2025)

Downregulation of SMAD2 and SMAD4 is associated with poor prognosis and shorter survival in esophageal squamous cell carcinoma - Jayasree Talukdar; Kangkana Kataki; Bikash Narayan Choudhury; Munindra Narayan Baruah; Mallika Bhattacharyya; Manash Pratim Sarma; Minakshi Bhattacharjee; Partha Pratim Das; Simanta Kalita; Subhash Medhi (Molecular Biology Reports, 2025)

Occurrence of Existing BCR-ABL Baseline Mutations and Associated Haplotype (NmR) Among CML Patients with Diverse IM Response: A Hospital-based Study from North-East India - Gautam Hazarika; Manash Jyoti Kalita; Partha Pratim Das; Simanta Kalita; Kalpajit Dutta; Lipika Lahkar; Anjanjyoti Rajkonwar; Mohammed Ghaznavi Idris; Vinotsale Khamo; Giriraj Kusre; Subhash Medhi (Biochemical Genetics, 2024)